How probiotics face food stress: They get by with a little help. Issue 9 (14th May 2020) - Fiocco, Daniela; Longo, Angela; Arena, Mattia Pia; Russo, Pasquale; Spano, Giuseppe; Capozzi, Vittorio
Abstract: The dietary consumption of probiotics in the form of pharmaceuticals or functional food can improve human health and contribute to disease prevention. However, the biological activity and health potential of food-delivered probiotics can be severely compromised by the stress conditions encountered by the microorganisms throughout the manufacture process, from probiotic preparation to their inclusion into food, subsequent storage and ingestion. Here, we give an account of the stress factors that can have major negative impacts on probiotic viability and functionality, with a focus on food-related environmental adverse conditions. We also describe some of the mechanisms elicited by the microbial cells to counteract these stresses and summarize a few relevant approaches proposed in literature to develop more robust and competitive probiotics by enhancing their stress tolerance, with the aim to improve the efficacy and health value of probiotic functional food.